1994
DOI: 10.1111/j.1465-7295.1994.tb01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Tools: Cooperative Learning in Economics

Abstract: Cooperative learning is a structured, systematic instructional technique in which students work together in small groups toward a common goal. We demonstrate the effectiveness of cooperative learning with an illustrative example for teaching the labor supply curve. Recommendations for introducing the technique, forming groups, the instructor's role during group work, grading and extensions of cooperative learning to other topics are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Slavin (1992) and Ravenscroft, Buckless, McCombs, and Zuckerman (1995) suggested that group grades must be assigned to promote shared responsibility to reinforce a more positive learning outcome. Fiechtner and Davis (1992), Maier and Keenan (1994), and Knabb (2000) suggested that in-class cooperative learning output should receive between 10 and 20% of the final grade.…”
Section: Time Value Of Classroom Engagementmentioning
confidence: 98%
“…Slavin (1992) and Ravenscroft, Buckless, McCombs, and Zuckerman (1995) suggested that group grades must be assigned to promote shared responsibility to reinforce a more positive learning outcome. Fiechtner and Davis (1992), Maier and Keenan (1994), and Knabb (2000) suggested that in-class cooperative learning output should receive between 10 and 20% of the final grade.…”
Section: Time Value Of Classroom Engagementmentioning
confidence: 98%
“…Co-operative or collaborative learning encompasses a large number of structured, systematic, in class techniques that engage students in group work toward a common goal (Maier and Keenan, 1994). According to Gerlach (1994), "collaborative learning is based on the idea that learning is a naturally social act in which the participants talk among themselves; it is through the talk that learning occurs".…”
Section: Background Literaturementioning
confidence: 99%
“…A collaborative approach to tutorials, also encourages deep learning and the development of improved communication and teamwork skills (Kagan, 1992). In fact, research shows that students collaborating in groups learn more, use higher level reasoning, are more satisfied with their classes, are less likely to drop out, and more tolerant of ethnic and racial differences (Maier and Keenan, 1994). Thus, the use of collaborative learning is essential when combined with PBL, as students discuss, explain and understand new ideas more freely.…”
Section: Background Literaturementioning
confidence: 99%
“…Mohatar (1994) argues that the activity eliminates memorization and repetition and gives students opportunities to interact with each other. Games and simulations also enable more positive student relationships, increase individual motivation, and promote a healthier psychological environment than any other classroom method (Maier and Keenan 1994;Chamberlin 1995;Lewis and Williams 1994).…”
Section: Introductionmentioning
confidence: 99%